Answer:
We know that the equation of the circle in standard form is equal to <em>(x-h)² + (y-k)² = r²</em> where (h,k) is the center of the circle and r is the radius of the circle.
We have x² + y² + 8x + 22y + 37 = 0, let's get to the standard form :
1 - We first group terms with the same variable :
(x²+8x) + (y²+22y) + 37 = 0
2 - We then move the constant to the opposite side of the equation (don't forget to change the sign !)
(x²+8x) + (y²+22y) = - 37
3 - Do you recall the quadratic identities ? (a+b)² = a² + 2ab + b². Now that's what we are trying to find. We call this process <u><em>"completing the square"</em></u>.
x²+8x = (x²+8x + 4²) - 4² = (x+4)² - 4²
y²+22y = (y²+22y+11²)-11² = (y+11)²-11²
4 - We plug the new values inside our equation :
(x+4)² - 4² + (y+22)² - 11² = -37
(x+4)² + (y+22)² = -37+4²+11²
(x+4)²+(y+22)² = 100
5 - We re-write in standard form :
(x-(-4)²)² + (y - (-22))² = 10²
And now it is easy to identify h and k, h = -4 and k = - 22 and the radius r equal 10. You can now complete the sentence :)
yes it is right when the vertex of the first polygon is located on 3 - 2 after rotation the work vertex will be there on (2 , 3) it is right
Answer:
C
Step-by-step explanation:
The car's average rate is 43.7 mph. The bicycle's average rate is 12.3 mph.
To get this solution, let the bicycle's average rate be (x) and the car's average rate be (x + 31.4) mph.
Distance= Speed x Time
364 = (x + x + 31.4) 6.5
364 = (2x + 31.4) 6.5
364/6.5 = 2x + 31.4
56 = 2x + 31.4
56 - 31.4 = 2x
24.6 = 2x
24.6/2 = x
12.3 = x
x = 12.3 mph
x+31.4 = 43.7 mph
True
plz thank me, it motivates me to answer more of your questions :)